Research and management techniques for the conservation of sea turtles. - Eckert, K.L., Bjorndal, K.A., Abreu-Grobois, F.A., and Donnelly, M. (eds.). (1999)
IUCN/SSC Marine Turtle Specialist Group Publication no. 4
Keywords: Wildlife conservation; Sea turtles; Sea turtles--Conservation.